Temperature behavior of the 4K-class Joule Thomson cooler during the cool-down phase for space science missions - Shinozaki, Keisuke; Suzuki, Toyoaki; Yamasaki, Noriko Y.; Sekimoto, Yutaro; Dotani, Tadayasu; Yoshihara, Keisuke; Sugita, Hiroyuki; Tsunematsu, Shoji; Kanao, Kenichi (Cryogenics (Guildford), 2024)
In space science missions that uses cryogen-free mechanical cooler systems for a low temperature telescope and the focal plane assembly, a cooling power from room temperature to cryogenic temperature is almost always critical for cooldown, and estimating the cooling time after launch is important because of the limited cooling power of mechanical coolers. This paper reports the experimental results of the 4K-class Joule Thomson cooler (4K-JT) during the cooldown phase, from 300 K to 20 K, and from precooling (about 20 K) to operating temperature with different precooling temperature and different heat loads. These results enable us to confirm the feasibility of the cryogenics design and to consider the realistic driving parameters during cooldown for future missions, such as LiteBIRD. •The experimental results of the space-qualified 4K-JT during the cooldown phase are reported.•The cooling time from 300 K to 20 K with the orifice is 8.5 times longer than that with the bypass line.•The 4K-JT could cool from 20 K to 5 K with the heat input of 8 mW even with reduced driving power.•The precooling temperature must be fitted for estimating the cooling capability with two heater measurements.